COVID-19 and Solid Organ Transplantation: A Review Article. Issue 1 (2nd November 2020) - Azzi, Yorg; Bartash, Rachel; Scalea, Joseph; Loarte-Campos, Pablo; Akalin, Enver
Abstract : The coronavirus pandemic has significantly impacted solid organ transplantation (SOT). Early in the outbreak period, transplant societies recommended suspending living kidney transplant programs in communities with widespread transmission to avoid exposing recipients to increased risk of immunosuppression, while recommendations were made to reserve deceased-donor kidney transplantation for likely life-saving indications. SOT recipients may be at high risk from COVID-19 disease due to chronic immunosuppressive treatment and other medical comorbidities. Mortality rates reported between 13 to over 30% in SOT recipients. In addition to high rates of complications and mortality attributable to COVID-19 infections, the pandemic has also led to additional complexities in transplantation including new questions regarding screening of donors and recipients, decision making to accept a patient for kidney transplant or wait after pandemic. The clinical implications of COVID-19 infection may also differ depending on the type of the transplanted organ and recipient comorbidities which further impacts decisions on continuing transplantation during the pandemic. Transplant activity during a pandemic should be tailored with careful selection of both donors and recipients. Furthermore, while tremendous strides have been made in treatment strategies and vaccinations, the impact of these in transplant recipients may be attenuated in the setting of their immunosuppression. In this review, we aim to summarize several aspects of COVID-19 in transplantation, including the immune response to SARS-CoV-2, SARS-CoV-2 diagnostics, clinical outcomes in SOT recipients, and end-stage kidney disease patients, transplant activity during the pandemic, and treatment options for COVID-19 disease.